Why do we complicate the solution of the problem? reflection of Finnish students and teachers on a mathematical summer camp - Ambrus, András; Hortobágyi, István; Näätänen, Marjatta; Liira, Riitta; Salmela, Maija (Teaching Mathematics and Computer Science, 2006)
This paper deals with reactions and reflections of Finnish secondary school students and teachers on Hungarian mathematics teaching culture. The experiences were collected at a mathematics summer camp in Hungary.